Role of Some Monetary Indicators on Nepalese Economic Growth - Dhungel, Bashu Dev (Humanities and Social Sciences Journal, 2021)
This research paper attempts to examine the causal association between major’s Nepalese monetary factors and Gross Domestic Product growth from 1980–2019. To confirm the short-term and long-term contribution of monetary factors to Gross Domestic Product Growth, Johansen approach to cointegration and Error Correction Model has employed and the results have confirmed that the broad money supply and consumer price index positively and significantly affects Gross Domestic Product growth whereas bank rate is seemed to be negatively and significantly effect on Gross Domestic Product growth in Nepalese economy. Moreover, Error Correction coefficient term (-0.4) confirms the emergence of a nexus between the monetary related variables and Gross Domestic Product growth at 40% speed of adjustments towards the equilibrium.